Research and policies on new communication technologies in Latin America: A personal reflection - Roncagliolo, Rafael (1988)
Topics and research methods are usually defined from outside the scientific life and community spheres. Difficult to find discipline or subject in which knowledge has been accumulated in a linear way, without dialectical leaps and, above all, without complex and mediated interactions with legitimate demands and questions generated from the social contour. This kind of universal constancy is particularly valid in the case of Latin America and for its young and uneven research on communications, within which new technologies have become a favorite focus.